2013
DOI: 10.1016/j.ejmech.2013.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship (SAR) and preliminary mode of action studies of 3-substituted benzylthioquinolinium iodide as anti-opportunistic infection agents

Abstract: Opportunistic infections are devastating to immunocompromised patients. And in especially sub-Saharan Africa where the AIDS epidemic is still raging, the mortality rate was recently as high as 70%. The paucity of anti-opportunistic drugs, the decreasing efficacy and the development of resistance against the azoles and even amphotericin B have stimulated the search for new drugs with new mechanisms of action. In a previous work, we showed that a new chemotype derived from the natural product cryptolepine displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The extraction and separation test revealed that it contains cryptolepine, neocryptolepine, quindoline, hydroxycryptolepine, and other ingredients. Further research revealed that the main component cryptolepine, whose total synthesis was prior to separation and determination, had exhibited unprecedented pharmacological effects, including antimalarial activity, antibacterial activity, anticancer activity, antifungal activity, anti-inflammatory activity, , antidiabetic activity, antituberculosis activity, and so on. Although fruitful achievements had been widely reported, the exploration of cryptolepine and its derivatives in fungicide chemistry was barely conducted. This implied us that more emphasis should be laid on the study of cryptolepine and its derivatives in the control of crop fungi.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction and separation test revealed that it contains cryptolepine, neocryptolepine, quindoline, hydroxycryptolepine, and other ingredients. Further research revealed that the main component cryptolepine, whose total synthesis was prior to separation and determination, had exhibited unprecedented pharmacological effects, including antimalarial activity, antibacterial activity, anticancer activity, antifungal activity, anti-inflammatory activity, , antidiabetic activity, antituberculosis activity, and so on. Although fruitful achievements had been widely reported, the exploration of cryptolepine and its derivatives in fungicide chemistry was barely conducted. This implied us that more emphasis should be laid on the study of cryptolepine and its derivatives in the control of crop fungi.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to constrained derivatives, only α-amidoboronic acids in five-membered boroproline motifs have been investigated. While variation in ring size and homologation strategies can modulate activity and selectivity of drug-like scaffolds, the available methodology does not allow for streamlined synthesis of constrained amidoboronic acids. Herein, we describe reactions that provide synthetic access to homologous BCN (boron–carbon–nitrogen) and BCCN (boron–carbon–carbon–nitrogen) motifs in various ring sizes.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2, compound 1 has been recognized as a versatile precursor to successfully achieve the corresponding arylation,5 alkenylation,6 alkynylation7 as well as the formations of CN,8 CO,9 and CS10 bonds. Since the iodine atom could not be replaced by other halogen atoms (such as Br and Cl)8a,c,10b,c in these couplings, the importance of the synthesis of 3‐iodoquinolines 1 has been enhanced significantly 11…”
Section: Introductionmentioning
confidence: 99%